A systematic review about organizational culture and the genesis of the burnout syndrome (Research, Society and Development, 2023)
This study aimed to investigate whether the organizational culture can, in fact, generate a direct impact on the mental and physical health of the employee, facilitating the development of the burnout syndrome. Thus, an attempt was made to clarify, through previously published studies, the situation of the work environments of health and education professionals; in order to observe if these can affect the health of the actors to the point that they develop the burnout syndrome. In this way, a systematic review was carried out, with the objective of defining what was previously specified, and understanding what can be done to mitigate this situation. Some articles were defined for the construction of the introduction, for a better understanding of the subject and, as discussion material, eight studies were selected, which address both the professionals' own view on the subject, as well as highlight the main causes of this scenario. In this context, it was possible to infer that this is an extremely serious and urgent problem, subject to greater organizational/professional attention.